Leishmaniasis: General Aspects Related with the Disease, the Parasite Cycle, Available Drugs, Novel Prototypes and Vaccines - Blanco, Vinicius R. [UNESP]; Nascimento-Junior, Nailton M. [UNESP] (Brazilian Chemical Soc, 2017)
Leishmaniasis is a neglected disease that has most part of the registered cases in third world countries and as well as other neglected diseases, low investment in research and development of new drugs is observed, especially because this disease affects mainly low-income population. In recent years, globalization and migration resulted in many demographic changes and the disease has become endemic in countries where only a handful of cases appeared. The main courses of treatment are extremely effective, but high prices and side effects made it difficult in some parts of the world to provide a suitable treatment, causing complications and the disease progress, in some cases leading to death. In this context, several research groups have been looking for new drug candidates from natural sources or drugs with antiparasitic effect. In this paper are discussed the main current treatments as well as novel compounds being developed, searching for alternatives with mild side effects and more effectiveness in comparison with the current treatments. The parasite cycle and a general understanding of the disease will also be discussed.
Keywords: Leishmaniasis; parasite cycle; bioactive compounds; structure-activity relationships